Accelerated bioethanol fermentation by using a novel yeast immobilization technique: Microtube array membrane - Chen, Chien-Chung; Wu, Chien-Hui; Wu, Jhih-Jhong; Chiu, Chien-Chih; Wong, Chien-Hsuan; Tsai, Min-Lang; Lin, Hong-Ting Victor (Process biochemistry (1991), 2015)
•A novel cell immobilization technique for bioethanol production was introduced.•Microtube array membrane was stable in 15% ethanol during shaking cultivation.•MTAM-encapsulated yeasts showed better bioethanol productivity. Cell immobilization is a way to isolate or localize intact cells in a certain space and maintain their catalytic activity. Immobilized cells can effectively reduce the negative effects of inhibitors and the processing cost of inoculum preparation for continuous or fed-batch fermentation of microorganisms. In this study, a novel yeast immobilization technique using renewable poly-l-lactic acid (PLLA) microtube array membrane (MTAM) was thoroughly evaluated for bioethanol fermentation. PLLA-MTAM was shown to be stable in 15% (v/v) ethanol solution during shaking cultivation. A yeast encapsulation efficiency of 67–70% was obtained, and the yeasts in MTAMs with greater porosity showed greater bioethanol productivity. The MTAM-immobilized Kluyveromyces marxianus, prepared using in situ and siphon methods, were evaluated using 5% (w/v) glucose fermentation. Improved glucose consumption and bioethanol production were observed in batch bioethanol fermentation. In 7 cycles during repeated-batch fermentation, the immobilized yeasts prepared using the in situ method showed a maximum CEtOH of 24.23g/L, maximum YP/S of 0.48g/g, and r PEtOH of 2.69g/L h. Our data indicated that the PLLA-MTAM immobilized yeasts significantly enhanced bioethanol productivity and was a novel, promising technology for bioethanol fermentation.